2011
DOI: 10.1557/mrs.2011.67
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of cell-cell signaling and motility to bacterial biofilm formation

Abstract: Many bacteria grow attached to a surface as biofilms. Several factors dictate biofilm formation, including responses by the colonizing bacteria to their environment. Here we review how bacteria use cell-cell signaling (also called quorum sensing) and motility during biofilm formation. Specifically, we describe quorum sensing and surface motility exhibited by the bacterium Pseudomonas aeruginosa, a ubiquitous environmental organism that acts as an opportunistic human pathogen in immunocompromised individuals. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
74
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(75 citation statements)
references
References 55 publications
0
74
0
1
Order By: Relevance
“…Since translocation on surfaces has important consequences with respect to surface colonization, this mechanism suggests a new strategy for community architecture development and subsequent biofilm formation (44). This and earlier work by O'Toole's laboratory (45) demonstrate key roles for P. aeruginosa flagellar motors in these processes.…”
mentioning
confidence: 52%
“…Since translocation on surfaces has important consequences with respect to surface colonization, this mechanism suggests a new strategy for community architecture development and subsequent biofilm formation (44). This and earlier work by O'Toole's laboratory (45) demonstrate key roles for P. aeruginosa flagellar motors in these processes.…”
mentioning
confidence: 52%
“…Cells move along the ECM through focal adhesions and specific recognition of ECM components. In bacteria, the ECM also promotes extracellular recognition, adhesion, and motility, allowing the formation of antibiotic-resistant biofilms (2). Therefore, functional studies of the ECM have received attention in many fields from cancer biology to bacteriology.…”
mentioning
confidence: 99%
“…However, the role of slime has never been addressed directly, leaving its propulsive contribution as an open question. Slime could also facilitate motility, promoting specific adhesion and allowing cellcell communication through the deposition of signaling molecules (2). In the past, slime has been observed by invasive techniques such as EM, nonspecific staining, or DIC on glass (6, 9) (see below), which prevented its analysis during the motility of live cells.…”
mentioning
confidence: 99%
“…The studies from Lehner et al (2005) demonstrated the ability of biofilm-producing strains of C. sakazakii to synthesize the cell signalling molecules acyl homoserine lactones (AHLs), which mediate quorum sensing (QS). This cell-to-cell signalling along with other genetic and environmental factors have been reported to be involved in biofilm formation in bacteria (Waters & Bassler, 2005;Shrout et al, 2011). Therefore, the interference with this phenomenon by means of quorum-sensing inhibitor (QSI) could be an attractive approach to prevent or to reduce biofilm-based infections.…”
Section: Introductionmentioning
confidence: 99%